2006
DOI: 10.4319/lo.2006.51.1.0021
|View full text |Cite
|
Sign up to set email alerts
|

Picophytoplankton cell death induced by UV radiation: Evidence for oceanic Atlantic communities

Abstract: We analyzed the effect of ambient levels of visible and ultraviolet radiation (UVR) on picophytoplankton cell death by exposing natural communities of picophytoplankton (Prochlorococcus, Synechococcus, and picoeukaryotic cells) from the Atlantic Ocean to different levels of natural solar radiation, from that received just below the surface to 23% lower levels and dark conditions. Underwater oceanic levels of UVR and visible light can induce significant cell death in picophytoplankton communities. The decay rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
116
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 34 publications
14
116
1
1
Order By: Relevance
“…Accordingly, it has previously been argued that the small size of picophytoplankton should be a disadvantage under high solar radiation exposure as pico-sized organisms may find it difficult to accommodate within their cells sufficient photoprotective substances to avoid photosynthetically active radiation and ultraviolet radiation damage (García-Pichel, 1994;Finkel et al, 2010). Llabrés and Agustí (2006) have demonstrated that natural levels of visible and ultraviolet radiation induce considerable picophytoplankton cell mortality in the subtropical Atlantic Ocean. In addition, Agustí and Llabrés (2007) reported that picophytoplankton experience high cell death rate due to exposure to natural underwater levels of solar radiation in the UML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it has previously been argued that the small size of picophytoplankton should be a disadvantage under high solar radiation exposure as pico-sized organisms may find it difficult to accommodate within their cells sufficient photoprotective substances to avoid photosynthetically active radiation and ultraviolet radiation damage (García-Pichel, 1994;Finkel et al, 2010). Llabrés and Agustí (2006) have demonstrated that natural levels of visible and ultraviolet radiation induce considerable picophytoplankton cell mortality in the subtropical Atlantic Ocean. In addition, Agustí and Llabrés (2007) reported that picophytoplankton experience high cell death rate due to exposure to natural underwater levels of solar radiation in the UML.…”
Section: Discussionmentioning
confidence: 99%
“…The potential causes of this pattern were explored by Fernández et al (2003), who concluded that a higher light utilization efficiency of the larger phytoplankton fraction in the oligotrophic waters could enhance its contribution to primary production in comparison with that of picophytoplankton. In addition, it has been demonstrated that solar radiation induces considerable cell damage and mortality in the subtropical Atlantic (Llabrés and Agustí, 2006;Agustí and Llabrés, 2007), and Teira et al (2005) hypothesized that a considerable fraction of the picophytoplankton biomass should correspond to damaged and non-viable cells, thus resulting in discrepancies between their contribution to biomass and carbon fixation. Pérez et al (2006) characterized the vertical variability of phytoplankton biomass, size structure, production and growth in the Atlantic subtropical gyres.…”
Section: Introductionmentioning
confidence: 99%
“…However, for simple organisms, especially phytoplankton, durations of hours or a few days are sufficient for serious effects to be observed (Boucher and Prezelin 1996;Neale et al 1998;Llabres and Agusti 2006;Kouwenberg et al 1999). Damage values in our modeling vary over timescales on order of weeks to a month.…”
Section: Confrontation Of Simulations With Datamentioning
confidence: 99%
“…It should be noted that field studies of the cell death of marine phytoplankton remain limited to several regions: the North Sea (van Boekel et al, 1992;Brussaard et al, 1995;Riegman and Winter 2003), the Adriatic Sea (Baldi et al, 1997), the Mediterranean Sea (Agustí et al, 1998;Agustí and Duarte, 2000;Agustí and Sánchez, 2002;Alonso-Laita et al, 2005), and the Atlantic Ocean (Veldhuis et al, 2001;Agustí, 2004;Alonso-Laita and Agustí, 2006;Llabrés and Agustí, 2006). No information was available on the cell death of phytoplankton in the Pacific Ocean.…”
Section: Introductionmentioning
confidence: 99%